(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: It is reasonable and important to optimize the diagnostic and surgical measures for faster visual rehabilitation of patients with posterior capsular cataract (PCC). Purpose: To investigate morphological changes (as assessed by optical coherence tomography (OCT)) in the posterior lens capsule (PLC) in PCC, and to assess their value in the optimization of phacoemulsification for these cataracts. Material and Methods: Of the 1780 eyes (1200 patients) with cataract examined, 512 eyes (28.8%) were diagnosed with PCC. Patients had OCT of the anterior segment (AS-OCT) and phacoemulsification. The morphological changes in the PLC as assessed by OCT, the course of surgical treatment and perioperative complications were reviewed. Results: Three types of morphological changes in the PLC were identified. Type 1 changes were characterized by a clear PLC margin and found in 312 of the 512 eyes (61%). A posterior capsule-sparing phacoemulsification (i.e., with low power, vacuum and irrigation settings) was used only in 28% of eyes. In type 2 changes, the PLC margin was not uniform in reflectivity and thickness, but appeared clear at the retrolenticular space. Type 2 changes were found in 185 of the 512 eyes (36%). We refrained from hydrodissection in 95.1% of cases, used a posterior capsule-sparing phacoemulsification in 97% of cases and posterior capsule polishing in all cases of PLC with type 2 changes. Type 3 changes were characterized by PLC bulging into the retrolenticular space, and were found in 15 eyes (3%). A capsule rupture was observed in 53% of eyes with type 3 changes, although we used a posterior capsule-sparing phacoemulsification with viscodilation in these cases. Conclusion: AS-OCT allows detailed assessment of morphological changes in the PLC and identification of three types of these changes. It is reasonable to take in account these facts when selecting a surgical treatment strategy.